Design, synthesis and biological evaluation of N-oxide derivatives with potent in vivo antileishmanial activity - Leandro da Costa Clementino (Public Library of Science (PLoS), 2021)
Leishmaniasis is a neglected disease that affects 12 million people living mainly in developing countries. Herein, 24 new N-oxide-containing compounds were synthesized followed by in vitro and in vivo evaluation of their antileishmanial activity. Compound 4f, a furoxan derivative, was particularly remarkable in this regard, with EC50 value of 3.6 μM against L. infantum amastigote forms and CC50 value superior to 500 μM against murine peritoneal macrophages. In vitro studies suggested that 4f may act by a dual effect, by releasing nitric oxide after biotransformation and by inhibiting cysteine protease CPB (IC50: 4.5 μM). In vivo studies using an acute model of infection showed that compound 4f at 7.7 mg/Kg reduced ~90% of parasite burden in the liver and spleen of L. infantum-infected BALB/c mice. Altogether, these outcomes highlight furoxan 4f as a promising compound for further evaluation as an antileishmanial agent.